What is the Role of Constraint-Induced Movement Therapy in Pediatric Rehabilitation? - (:unkn) unknown (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2013)
Constraint-induced movement therapy (CIMT) is one of the promising rehabilitation interventions for improving the function of the upper extremity (UE) in patients with hemiparesis. Basic CIMT protocol includes constraining the use of the less-impaired UE, intensive, repetitive practice of motor training with the impaired UE for 2-3 weeks, and shaping therapy. So far numerous case studies, randomized controlled trials have been reported about CIMT in children with cerebral palsy, stroke, traumatic brain injury and obstetric brachial plexus paralysis. Protocols vary widely in terms of type of constraint used, intensity and duration of training, and outcome measures. This article will review studies evaluating the efficacy of CIMT in improving the hemiplegic arm functioning and the application of CIMT in pediatric patients.
Keywords: Constraint-induced movement therapy; upper extremity; children; HEMIPLEGIC CEREBRAL-PALSY; UPPER-LIMB REHABILITATION; RANDOMIZED CONTROL TRIAL; CONGENITAL HEMIPARESIS; UPPER-EXTREMITY; YOUNG-CHILDREN; FORCED USE; EFFICACY; INTERVENTION; COORDINATION